Gratitude as an Affective Foundation of Religiosity: Evidence from Indonesian Majelis Taklim Communities - Gilang Tri Prayogo Yusuf; Prahastia Kurnia Putri (Universitas Ahmad Dahlan, 2026)
This study investigated the association between gratitude and religiosity among members of Islamic study groups (majelis taklim) in Indonesia. Using a quantitative cross-sectional design (N = 154), participants completed an 8-item Indonesian Gratitude Questionnaire derived from the GQ (McCullough et al., 2002) and its 11-item Indonesian adaptation (Grimaldy & Haryanto, 2020) and a modified 34-item Centrality of Religiosity Scale adapted for the Indonesian Islamic context (Huber & Huber, 2012; Purnomo & Suryadi, 2018). Simple linear regression examined the gratitude–religiosity relationship. Results showed gratitude was significantly associated with overall religiosity (β = .463, p < .001, 95% CI [1.11, 2.09]), explaining 21.4% of the variance (R² = .214). These findings suggest gratitude is meaningfully linked to religiosity in majelis taklim communities within collectivist Islamic contexts. Faith-based community programs and majelis taklim facilitators may consider integrating structured gratitude practices (e.g., brief reflective exercises, gratitude journaling, or group sharing) as a complementary strategy to strengthen religious engagement and social cohesion, while future studies should test causal mechanisms using longitudinal or intervention designs.